Porencephalic cyst as a cause of seizures in adults: a rare case report using MRI and cerebral angiography methods - Amran, Muhammad Yunus; Haurissa, David Christian; Soraya, Gita Vita (Journal of the Pakistan Medical Association, 2025)
A porencephalic cyst is a rare intracranial lesion characterised by a cerebrospinal fluid-filled cavity within the cerebral hemisphere, typically surrounded by gliotic or spongiotic white matter. These cysts often present with neurological symptoms such as seizures, developmental delays, or motor impairments, depending on their size and location. We present the case of a 19-year-old male with a three-month history of recurrent seizures. Initial management with valproic acid led to significant improvement, with the patient remaining seizure-free during follow-up. Cerebral MRI revealed a porencephalic cyst with a mural nodule in the left temporo-occipital region; however, angiographic studies demonstrated no vascular abnormalities. Treatment approaches for porencephalic cysts are primarily symptomatic, including the use of antiepileptic medications and physiotherapy to address motor deficits. Surgical intervention may be considered in cases complicated by hydrocephalus or raised intracranial pressure. This case underscores the importance of tailored management strategies in achieving optimal outcomes. Keywords: MRI of the head, Cerebral angiography, Porencephalic cyst, Seizure.